Hubungan Pengetahuan dan Pola Asuh Orang Tua dengan Teknik Menyikat Gigi yang Benar Pada Anak Prasekolah di TK Negeri Bintaro Kota Jakarta Selatan - Susanti Widiastuti; Nur Fajariyah; Rizka Olivia (Universitas Malahayati Lampung, 2024)
ABSTRACT Parents are the main determinants of their children’s oral hygiene at preschool age. The prevalence of oral and dental problems in DKI Jakarta Province is 59,13% with the proportion of correct tooth brushing in South Jakarta City only 3,33%. So that control efforts are needed such as the selection of toothbrushes, the use of toothpaste, the correct brushing technique, the frequency of brushing and diligent control to the dentist to maintain oral hygiene. To identify the relationship between knowledge and parenting with tooth brushing technique in pre-school student of playground Bintaro South Jakarta. Quantitative correlational research design with a cross-sectional analytic approach. Knowledge was measured using a knowledge questionnaire, parenting styles were measured using The Parenting Styles and Dimension Questionnaire (PSDQ), and correct tooth brushing techniques were measured using an observation sheet. The majority of the respondents were female (88%), the average age was 31 with SD 3.338, and Bachelor education (54.7%). The majority of respondents had good knowledge (56.0%) and authoritative parenting (73.3%). The correct tooth brushing technique in children is lacking (73.3%). The results of the chi-square statistical test analysis in no relationship between knowledge and parenting with tooth brushing technique in pre-school student of play ground Bintaro South Jakarta City with a p-value of 0.920 and 0.655 α = 0.5. It is expected that school will collaborate with the health services to conduct counseling related to correct tooth brushing techniques in preschool children. Keywords: Knowledge, Parenting, Tooth Brushing Technique ABSTRAK Orang tua merupakan penentu utama kebersihan gigi dan mulut anak-anak mereka di usia prasekolah. Pravelensi yang mengalami permasalahan gigi dan mulut di Provinsi DKI Jakarta sebesar 59,13% dengan proporsi menyikat gigi yang benar di Kota Jakarta Selatan hanya sebesar 3,33%. Sehingga diperlukan upaya pengendalian seperti pemilihan sikat gigi, penggunaan pasta gigi, teknik menyikat gigi yang benar, frekuensi menyikat gigi dan rajin kontrol ke dokter gigi untuk menjaga kebersihan gigi dan mulut. Menganalisa hubungan pengetahuan dan pola asuh orang tua dengan teknik menyikat gigi yang benar pada anak prasekolah di TK Negeri Bintaro Kota Jakarta Selatan. Desain penelitian korelasional kuantitatif dengan pendekatan analytic cross-sectional. Pengetahuan diukur menggunakan kuesioner pengetahuan, pola asuh orang tua diukur menggunakan kuesioner The Parenting Styles and Dimension Questionnaire (PSDQ), dan teknik menyikat gigi yang benar diukur menggunakan lembar observasi. Mayoritas responden berjenis kelamin perempuan (88%), rata-rata usia responden 31 dengan SD 3,338 dan berpendidikan S1 (54,7). Kemudian, mayoritas responden memiliki pengetahuan baik (56,0%) dan pola asuh orang tua authoritative (73,3%). Teknik menyikat gigi yang benar pada anak kurang (73,3%). Hasil analisis uji statistic chi-square menghasilkan tidak ada hubungan pengetahuan dan pola asuh orang tua dengan teknik menyikat gigi yang benar pada anak prasekolah di TK Negeri Bintaro Kota Jakarta dengan nilai p value 0,920 dan 0,655 α = 0,5. Diharapkan Dinas Kesehatan dan Puskemas bekerjasama dengan sekolah dapat mengadakan penyuluhan terkait teknik menyikat gigi yang benar pada anak prasekolah. Kata Kunci: Pengetahuan, Pola Asuh Orang Tua, Teknik Menyikat Gigi yang Benar